NEUROPSYCHOLOGICAL STATUS IN CHILDREN WITH BRONCHIAL ASTHMA (Multidisciplinary Journal of Science and Technology, 2025)
Bronchial asthma (BA) is one of the most common chronic diseases in children, exertinga significant impact not only on the respiratory system but also on the child’s neuropsychological624ISSN: 2582-4686 SJIF 2021-3.261,SJIF 2022-2.889, 2024-6.875 ResearchBib IF: 9.948 / 2024 VOLUME-5, ISSUE-10 state. This article examines the pathogenetic mechanisms of neurocognitive and psychoemotionaldisorders in children with BA, including chronic inflammation, hypoxia, therapy effects, and externalfactors. Based on an analysis of Uzbek and international literature, cognitive deficits such asimpairments in memory, attention, and executive functions are highlighted, along with an increasedrisk of comorbid psychiatric disorders, including ADHD and depression. The clinical outcomes andrecommendations for an integrated treatment approach focusing on screening and risk minimizationare discussed. The article emphasizes the need for further research to develop personalized strategiesfor improving patients’ quality of life.